Experimental determination of the residual compressive strength of concrete columns subjected to different fire durations and load ratios - Nair, Anjaly (My University, 2019)
The superior thermal property of concrete associated to its great capability of thermally insulating the embedded reinforcing steel rebar is the main reason for the good behavior of reinforced concrete structural elements in fire condition, compared to other construction materials. However, at elevated temperatures, concrete still undergoes changes in its mechanical and thermal properties, which mainly cause degradation of strength and may lead to the failure of the structure. Retrofitting is a desirable alternative to rehabilitate post-fire concrete structures. However, in order to ensure safe reuse of fire-exposed buildings and to adopt proper retrofitting methods, it is essential to evaluate the residual strength capacity of fire-damaged reinforced concrete structural elements. The focus of this experimental research study is to investigate the fire performance of reinforced concrete columns exposed to elevated temperatures that followed CAN/ULC-S101 standard fire, and then evaluate their residual compressive strengths after fire exposure. In order to effectively study the fire performance of such columns, eight identical 200 x 200 x 1500mm high reinforced-concrete column test specimens were subjected to two different durations of standard fire exposure (1 hour and 2 hours) while being loaded with two different axial load ratios (20% and 40% of the column ultimate design axial compressive load capacity). In a subsequent stage and after complete cooling down, residual compressive strength capacity tests were performed on the fire-exposed columns. Experimental results showed that the residual compressive strength capacity dropped to almost 50% and 30% of its ambient temperature capacity for the columns exposed to 1- and 2-hour fire durations, respectively. It was also noticed that the applied load ratio has less effect on the column’s residual compressive strength compared to that of the fire duration.
Keywords: Concrete (construction); Fire performance of reinforced concrete columns; Behaviour of concrete at high temperatures; Residual strength of fire-exposed concrete columns; Fire resistance testing